2006
DOI: 10.4028/0-87849-991-1.63
|View full text |Cite
|
Sign up to set email alerts
|

Solidification of Hypereutectic Thin Wall Ductile Cast Iron

Abstract: Abstract. Hypereutectic ductile iron was cast in green sand moulds with four plates with thickness of 1.5, 2, 3 and 4 mm in each mould. Temperatures were measured in the 3 and 4 mm plate. The temperature curves showed that eutectic solidification was divided into two stages: primary and secondary eutectic solidification. The first stage, which was relatively short, had none or very little recalescence. Further under cooling, followed by reheating during recalescence, was necessary to initiate the second part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…They have also made simulations of how the TC influences the temperature locally in thin walled ductile iron castings. 8,9 The simulations showed that the shape of the measured cooling curve is correct in comparison with the cooling curve in an unaffected casting. There was however a 15 to 20 uC parallel shift towards lower temperatures on the measured cooling curve in plate thicknesses of 2 to 4 mm.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…They have also made simulations of how the TC influences the temperature locally in thin walled ductile iron castings. 8,9 The simulations showed that the shape of the measured cooling curve is correct in comparison with the cooling curve in an unaffected casting. There was however a 15 to 20 uC parallel shift towards lower temperatures on the measured cooling curve in plate thicknesses of 2 to 4 mm.…”
Section: Introductionmentioning
confidence: 80%
“…This corresponds very well with what was shown by the numerical simulations. 8,9 Discussion Effect of segregation During solidification there can be some segregation of Si to the austenite. This would lower the Si content of the liquid and by that increase the T EW .…”
Section: Growth Undercoolingmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample rate for temperature measurement was 500 Hz and every 100 values were averaged to reduce noise giving a time increment of 0?2 s. The measured temperatures were corrected for the measurement error caused by the response time of the thermocouple. [3][4][5] The temperature was measured in all plates except for the 1?5 mm plates.…”
Section: Methodsmentioning
confidence: 99%